Cost benefit analysis of mesh reinforcement of stapled left pancreatectomy. Issue 11 (20th February 2013) - Idrees, Kamran; Edler, Joshua R.; Linehan, David C.; Strasberg, Steven M.; Jacques, David; Hamilton, Nicholas A.; Fields, Ryan C.; Lambert, Dennis; Kymes, Steven; Hawkins, William G.
Abstract Objectives Pancreatic leak is a morbid complication following left pancreatectomy, which results in prolonged hospitalization, additional diagnostic testing and invasive procedures. The present authors have previously demonstrated that mesh reinforcement of stapled left pancreatectomy results in fewer pancreatic leaks. This study was conducted to investigate whether mesh reinforcement also results in cost benefits for the health care system. Methods A cost benefit model was developed to estimate net cost savings from the payer's perspective. The model is based on the results of a randomized, single‐blinded trial of mesh versus no mesh reinforcement of the pancreatic remnant after left pancreatectomy. A two‐way sensitivity analysis was conducted to determine the model's sensitivity to fluctuations in the cost of mesh and the effectiveness of the mesh in reducing clinically significant leaks. Results Average total costs for an episode of care were US$13 337 and US$15 505 for patients who did and did not receive mesh, respectively, which indicates savings of US$2168. Two‐way sensitivity analysis showed that, given a probability of 1.9% for developing a clinically significant leak in patients in whom mesh reinforcement was used, the strategy would continue to save costs if mesh were priced at ≤US$1804. Conclusions Mesh reinforcement decreases clinically significant pancreatic leaks. Despite the additional cost of mesh reinforcement, the use of mesh reinforcement results in overall cost savings for the health care system because of the resultant decrease in the occurrence of clinically significant leaks.